2017
DOI: 10.1002/rcm.8005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope analysis of levoglucosan, a tracer of wood burning, in experimental and ambient aerosol samples

Abstract: Low oxygen isotope fractionation between cellulose and levoglucosan and clear differences in levoglucosan δ O values between the Swiss and Lithuanian ambient samples demonstrate that our new method is useful for source appointment studies on wood-burning-derived aerosols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…It is currently unclear which leaf functional traits influence uptake and incorporation of the temporal variations in δ 18 O V into the δ 18 O values of leaf water and assimilates (Kim & Lee, 2011;Lehmann et al, 2018;Roden & Ehleringer, 1999). A general survey of plant species of different growth forms covering a broad range of functional traits may therefore allow the identification of important drivers of 18 O-signal transfer processes and improve the climatic and physiological interpretation of δ 18 O signals in plant organic material and compounds, such as the δ 18 O of leaf and treering cellulose (Helliker, 2014;Helliker & Griffiths, 2007;Roden & Ehleringer, 1999) or δ 18 O of levoglucosan (Blees et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unclear which leaf functional traits influence uptake and incorporation of the temporal variations in δ 18 O V into the δ 18 O values of leaf water and assimilates (Kim & Lee, 2011;Lehmann et al, 2018;Roden & Ehleringer, 1999). A general survey of plant species of different growth forms covering a broad range of functional traits may therefore allow the identification of important drivers of 18 O-signal transfer processes and improve the climatic and physiological interpretation of δ 18 O signals in plant organic material and compounds, such as the δ 18 O of leaf and treering cellulose (Helliker, 2014;Helliker & Griffiths, 2007;Roden & Ehleringer, 1999) or δ 18 O of levoglucosan (Blees et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further work needs to be done to meet the requirements for more complex samples. Recently, Blees et al reported methylation of levoglucosan catalyzed by dimethyl sulfide for oxygen isotope measurement by gas chromatography/pyrolysis isotope ratio mass spectrometry [26]. Since methylation of levoglucosan introduces only three carbon atoms, it could be an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the oxygen isotopic composition (here given as the δ 18 O value) of plant‐derived compounds is widely used for the reconstruction of climatic, hydrological, and physiological changes 1–8 . Variations in the δ 18 O values of plant compounds are mainly caused by corresponding variations in the δ 18 O values of their source and leaf water 5,9 .…”
Section: Introductionmentioning
confidence: 99%